ᵃʳᶜʰPbWO₄ with improved optical parameters from archaeological lead - Yakubovskaya, A.G.; Tupitsyna, I.A.; Dubovik, A.M. (Вопросы атомной науки и техники, 2022)
Technological principles of manufacturing a lead tungstate crystal from archaeological lead for use in low-background experiments to search for rare events are presented. The influence of the conditions for obtaining single crystals of ᵃʳᶜʰPbWO₄ on the photochromic effect in single crystals is investigated. By minimizing deviations from the stoichiometric composition, it was possible to improve the optical parameters of the lead tungstate single crystal. Single crystals with improved optical parameters have been obtained using double crystallization and the introduction of an excess of ᵃʳᶜʰPbO, which makes it possible to consistently influence various defects in crystals of ᵃʳᶜʰPbWO₄. Наведено технологічні основи виготовлення кристала вольфрамату свинцю з археологічного свинцю для застосування в низькофонових експериментах із пошуку рідкісних подій. Досліджено вплив умов одержання монокристалів ᵃʳᶜʰPbWO₄ на фотохромний ефект у монокристалах. Шляхом мінімізації відхилень від стехіометричного складу вдалося поліпшити оптичні параметри монокристала вольфрамату свинцю. Одержані монокристали із застосуванням подвійної кристалізації та введенням надлишку ᵃʳᶜʰPbO дозволяють послідовно впливати на різні дефекти в кристалах ᵃʳᶜʰPbWO₄ з покращеними характеристиками. Приведены технологические основы изготовления кристалла вольфрамата свинца из археологического свинца для применения в низкофоновых экспериментах по поиску редких событий. Исследовано влияние условий получения монокристаллов ᵃʳᶜʰPbWO₄ на фотохромный эффект в монокристаллах. Путем минимизации отклонений от стехиометрического состава удалось улучшить оптические параметры монокристалла вольфрамата свинца. Полученные монокристаллы с применением двойной кристаллизации и введением избытка ᵃʳᶜʰPbO позволяют последовательно влиять на различные дефекты в кристаллах ᵃʳᶜʰPbWO₄ с улучшенными характеристиками.